Sumbangan Sektor Pariwisata Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Pacitan - Hidup Marsudi (STIE Atma Bhakti, 2025)
Pacitan Regency is a small regency that has various tourism potentials in it, ranging from natural tourism to cultural tourism. This study aims to determine the effect of the number of tourist visits, the number of hotel rooms and the number of tourist attractions on the original regional income of the tourism sector of Pacitan Regency for the period 2019-2024. The object of this study is income in the tourism sector of Pacitan Regency. The data used in this study are secondary data taken from the Central Statistics Agency (BPS) and the Pacitan Regency Tourism Office. This study uses multiple linear regression data analysis.Based on the analysis that has been carried out, the results obtained show that together the three variables have a significant effect with the results of the Adjusted R square test of 90.1% on the original regional income of the tourism sector, while the remaining 9.9% is influenced by variables outside those studied. Partially, only the variable number of tourist visits shows a positive and significant effect on the original regional income of the tourism sector of Pacitan Regency, while the variables number of hotel rooms and number of tourist attractions have a positive but not significant effect on the original regional income of the tourism sector of Pacitan Regency.